Pedagogies of Resistance: Living Resistance by Writing - Danielle E. Lorenz (Canadian Society for Studies in Education, 2018)
The focus of this (English) Special Issue is to provide an academic space for junior scholars to bring foreword the perspectives, histories, and knowledges that have traditionally been excluded from mainstream Canadian educational discourses. Through their writing the authors in this issue have situated anti-oppressive pedagogies into their individual praxes. This is demonstrated by examining the tensions that exist between Chinese Confucian-based pedagogies and Communicative Language Teaching (Gao); experiencing the pedagogical interventions intent in the Walking With Our Sisters memorial exhibit (McKinley); engaging in narrative inquiry to outline the ongoing colonialism within systems of education in the United Kingdom, the United States, and Canada (Mir); challenging how white settler colonial norms have manifested in Canadian university hiring demographics (Abwi); confronting the hegemonic masculinity of the Ultimate Fighting Championship while contrasting it with the need for wellness-based martial arts practice for gay male youth (Chan); and advocating for the importance of Marie Battiste’s “Visioning a Mi’kmaw Humanities: Indigenizing the Academy” edited collection (Downey).